2020
DOI: 10.1039/d0ma00593b
|View full text |Cite
|
Sign up to set email alerts
|

One-pot hydrothermal synthesis of molybdenum nickel sulfide with graphene quantum dots as a novel conductive additive for enhanced supercapacitive performance

Abstract: We depict a facile as well as an economical one-step hydrothermal method for the first time to synthesize a hierarchical three-dimensional (3D) flower-like structure of Molybdenum (Mo) particles decorated nickel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 69 publications
2
17
0
Order By: Relevance
“…Lei et al [ 8 ] reported that the energy and power densities of heteroatom-doped porous-biochar-based SC were in the range of 12.8–6 Wh kg −1 and 0.05–5 kW kg −1 , respectively. These results explicitly signify that the Er 10-GQD/HPB||HPB electrode material is a superior electroactive material to the symmetric HPB||HPB and to the various, previously reported, heteroatom-doped metal oxide/porous biochar nanocomposites and GQD nanomaterials [ 8 , 14 , 43 , 45 , 46 , 47 ].…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Lei et al [ 8 ] reported that the energy and power densities of heteroatom-doped porous-biochar-based SC were in the range of 12.8–6 Wh kg −1 and 0.05–5 kW kg −1 , respectively. These results explicitly signify that the Er 10-GQD/HPB||HPB electrode material is a superior electroactive material to the symmetric HPB||HPB and to the various, previously reported, heteroatom-doped metal oxide/porous biochar nanocomposites and GQD nanomaterials [ 8 , 14 , 43 , 45 , 46 , 47 ].…”
Section: Resultssupporting
confidence: 70%
“…Mane et al [ 14 ] used 3%La–MnO 2 @GO fabricated symmetric SC, and the energy and power densities were in the range of 64−10 Wh kg −1 and 1–1.5 kW kg −1 , respectively. When Sangabathula et al [ 45 ] combined GQDs with a Mo-doped nickel sulfide (MNS-G) nanocomposite as the electrode material for an asymmetric supercapacitor, the energy density was 38.9–11.1 Wh kg −1 and the power density of 0.4–6.7 kW kg −1 . Lei et al [ 8 ] reported that the energy and power densities of heteroatom-doped porous-biochar-based SC were in the range of 12.8–6 Wh kg −1 and 0.05–5 kW kg −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the presence of Mo­(IV) (confirmed by XPS) and sulfide content improves the electrical conductivity of the hybrid material. The detailed electrochemical redox reactions of the Zn-Ni LDH@NiMoS x electrode can be expressed by following equations: ,,,, Zn ions enhance the interaction between electro-active sites and reactants during the electrochemical redox reactions. , Furthermore, the Zn in the LDH component and MoS x do not exhibit any Faradaic redox reaction; however, they can allow insertion/deinsertion of the K + ion by forming a double layer at the electrode/electrolyte junction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the presence of Mo(IV) (confirmed by XPS) and sulfide content improves the electrical conductivity of the hybrid material. The detailed electrochemical redox reactions of the Zn-Ni LDH@NiMoS x electrode can be expressed by following equations: 1,5,8,46,47…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation